ON A LARGE SUNFISH RANZANIA TYPUS FROM THE SOUTHWEST COAST - Ebenezer, I P; Joel, J Jerold (Indian Journal of Fisheries, 2011)
A sunfish (or trunkfish), Ranzania typus, measuring 616 mm total length and a maximum depth of 310 mm was caught at Erayumanthurai on the southwest coast (Kanyakumari district, Tamil Nadu) on 2-3-1984 in a shore seine. The gear had operated a distance of 1 km from the shore, up to a depth of 22 m. Coloured bluish, tending towards dark above and to silvery below, it had a smooth skin with small hexagonal plates. Six streaks of lighter colour with darker borders, emanated from near the dorsal margin between the snout and the gill slit, curved downwards to the ventral profile. The posterior three streaks were branched and contained dark spots, mostly round. Lips were produced forwards beyond teeth as a funnel, closing in a vertical slit.